EFFECTIVENESS OF TRADITIONAL ENGKLEK GAMES TO IMPROVE SOCIAL SKILLS OF GROUP B CHILDREN AT TK AL-FATH PRESCHOOL BANDA ACEH - Cut Fazlil Hanum; Rini Rovika (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The background in this study is that children have low social skills such as not wanting to cooperate with groups, and not wanting to socialize with other children. Therefore the problem formulation of this study . "Is the application of traditional cricket games effective for improving the social skills of group B children at Al-Fath Preschool Banda Aceh?". So that the purpose of this study is to determine whether the application of traditional cricket games is effective for improving the social skills of group B children at Al-Fath Preschool Banda Aceh. Then, the research approach is quantitative and the type of research is experimental research. The sample used in this study was group B with a total of 10 children. Furthermore, the instruments used are observation and documentation. From the results of data analysis by calculating the t-test, the research results show that t count ≥ t (1-α) is 26.75 ≥ 1.83, then Ho is rejected and H1 is accepted. Therefore It can be concluded that the application of traditional cricket games is effective for improving the social skills of group B children at Al-Fath Preschool Banda Aceh. Therefore, traditional cricket games can be applied at school so that children are able to cooperate, be generous, desire for social acceptance, friendly attitude, and selflessness.